The Influence of Reward, Punishment, and Work Motivation on Employee Performance at MSMEs Palopo - Anggi Ka’ti; J. Junaidi; Jumawan Jasman (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of reward and punishment as well as work motivation on employee performance in Micro, Small, and Medium Enterprises (MSMEs) in the City of Palopo. This research uses a quantitative approach with the entire population of SMSEs employees in the City of Palopo. Primary data were collected thru questionnaires from 134 respondents selected using purposive sampling techniques, while secondary data were obtained from relevant literature studies. Data analysis was conducted using the covariance-based Structural Equation Modeling (SEM) method with the assistance of IBM SPSS AMOS version 22 and IBM SPSS Statistics version 22 software. The research results show that reward and punishment have a negative and insignificant effect on employee performance. Work motivation has also not been proven to have a significant direct effect on employee performance. However, punishment has been proven to have a positive and significant effect on work motivation, while reward has a negative and insignificant effect on work motivation. Work motivation has been shown to significantly mediate the effect of reward and punishment on employee performance. These findings underscore the important role of work motivation as a key mechanism in bridging reward and punishment policies toward improving employee performance. Therefore, proper management of rewards and punishments should focus on efforts to build work motivation so that the performance of MSMSEs employees in Palopo City can improve sustainably.